The correlation of nutritional status with hematology toxicity of adjuvant chemotherapy in ovarian cancer - Kadek Dharma Widhiarta; Brahmana Askandar (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHTS1. This retrospective cohort study found an increase in the diagnosis of malnutrition between the IMT method and NRI.2. A significant correlation was found between preoperative malnutrition and the incidence of anaemia after adjuvant chemotherapy for ovarian cancer patients.3. There were no significant correlations in this study in the incidence of leukopenia and thrombocytopenia.ABSTRACTObjectives: To observe correlation of nutritional status using Nutritional Risk Index with the side effects of adjunctive haematological chemotherapy.Materials and Methods: This study was a retrospective cohort study observing whether or not hematologic side effects occurred during chemotherapy based on medical records of postoperative ovarian cancer patients receiving adjuvant chemotherapy.Results: Sixty-eight subjects with age range of 31-50 years (44.1%) multipara (68.8%), and advanced stage (52.1%) were observed. An increase was found in the diagnosis of malnutrition between the IMT method and NRI, which was 18.7% compared to 43.7%. A significant correlation was found between preoperative malnutrition and the incidence of anaemia after adjuvant chemotherapy for ovarian cancer patients (p=0.002). Whereas, in the event of leukopenia and thrombocytopenia, there were no significant correlations with p=0.675 and p=0.415, respectively.Conclusion: There was an increase in malnutrition rate with the use of NRI compared with BMI and there was a significant correlation between malnutrition and side effects of anaemia in patients with ovarian cancer who underwent surgery and continued with adjuvant chemotherapy.